Post-buckling transition of compressed pipe strings in horizontal wellbores - Zhang, Qiang (2021)
In offshore oil and gas wells, the post-buckling transition of compressed pipe strings is a significant engineering problem to be addressed, particularly in horizontal wellbores. Many hypotheses exist in theoretical research, and it remains difficult to accurately measure the post-buckling mode in experimental tests. In the current study, the compressed pipe strings initially located at the bottom of horizontal wellbores were discretized into beam elements, and a gap element was introduced to detect the contact between the horizontal strings and the wellbores. The dynamic relaxation algorithm was used in finite element analysis to improve the weak points of the theoretical and experimental research. The calculation results show that the post-buckling transition exhibits nonlinearity. Based on the calculated post-buckling modes, the dimensionless critical loads for sinusoidal and helical buckling were identified. After sinusoidal buckling, it was observed that the compressed string was not in continuous contact with the horizontal wellbore, and two non-contact sections appeared near the string ends. These numerical results are beneficial for understanding the post-buckling behaviors of horizontal strings in wellbores.